Analisis pengaruh kebijakan investasi dan pembiayaan modal kerja terhadap profitabilitas perusahaan sub sektor kosmetik dan peralatan rumah tangga di Indonesia periode 2014-2019 - Dewi, Endah; Maharani, Maharani (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Maximizing company profitability has become a financial metric to see potential profits. This study aims to examine the effect of Aggressive Investment Policy (AIP) and Aggressive Financial Policy (AFP) on the company's profitability as measured by the Return on Asset Ratio (ROA). The sample of this study has 5 companies in the Cosmetics and Household Appliances Sector in Indonesia with the criteria of having short-term debt and current assets during the 2014-2019 period. With the classical assumption test technique and multiple linear regression test through SPSS 24, which shows the final result of the H1 study is accepted, it states that AIP and AFP have a significant or simultaneous effect on ROA.